LUAS DEFEK MENINGOKEL BERHUBUNGAN DENGAN KADAR TRANSFORMING GROWTH FACTOR β1 (TGF-β1)DAN INSULINE-LIKE GROWTH FACTOR-1 (IGF-1) DALAM TULANG - E.S., Moch. Istiadjid (Fakultas Kedokteran Universitas Brawijaya, 2004)
Meningocele pathogenesis is based on skull defect that occurs since the first three month of fertilization period. Through that defect, mening, cerebrospinal liquid, and cerebral parenchym is protruded. Meningocele can cause by folic aciddeficiency that had proved correlation with TGF-β1 and IGF-I level, both in maternal blood or baby rat’s skull. Folic acid deficiency also causes increasing the number of apoptosis and necrosis cells death in baby’s skull. TGF-β1 and IGF-I one growth factors thatstimulate bone synthesis. The purpose of this study is to explore the correlationbetween TGF-β1 and IGF-I level in skull on side defect of meningocele patients and the wide of skull defect to obtain the role of the two growth factors in meningocele teratogenesis perspectively. Eight meningocele patients that were performed excision by standard procedure have taken a few of bone speciment on sidedefect to count TGF-β1 and IGF-I levels with immunochemistry technic. Wide defect was determined by measuring defect’s diameter, using Martin anthropometer. The correlation between TGF-β1 and IGF-I skull level and defect’s wide was analyzed by SEM (structuralequation modeling) statistic. There was significant negative-correlation between that variable, that mean the lower of the two growth factors level is wider of skull defect. TGF-β1: r = -0.648, p =0.009; IGF-I: r = -0.426, p =0.025. Key words:Meningoencephalocele, Skull defect, TGF-β1, IGF-I.